2018
DOI: 10.3390/pharmaceutics10020042
|View full text |Cite
|
Sign up to set email alerts
|

Alginate in Wound Dressings

Abstract: Alginate is a biopolymer used in a variety of biomedical applications due to its favourable properties, such as biocompatibility and non-toxicity. It has been particularly attractive in wound healing applications to date. It can be tailored to materials with properties suitable for wound healing. Alginate has been used to prepare different forms of materials for wound dressings, such as hydrogels, films, wafers, foams, nanofibres, and in topical formulations. The wound dressings prepared from alginate are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
338
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(394 citation statements)
references
References 75 publications
3
338
0
6
Order By: Relevance
“…When applied to a wound, the calcium in the alginate reacts with the sodium salts present in the wound exchanges, forming sodium alginate, which is a hydrophilic gel (Lee and Mooney, 2012). Alginate is a naturally occurring biopolymer that is sourced from brown algae (Phaeophyceae), including Ascophyllum nodosum, Laminaria hyperborea, Laminaria japonica, Macrocystis pyrifera, and Laminaria digitate (Aderibigbe and Buyana, 2018). Soluble sodium alginate gel forms as a result of an active ion exchange of calcium ions for sodium ions at the wound surface, resulting in absorption of fluid at the wound site (Aderibigbe and Buyana, 2018).…”
Section: General Description and Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…When applied to a wound, the calcium in the alginate reacts with the sodium salts present in the wound exchanges, forming sodium alginate, which is a hydrophilic gel (Lee and Mooney, 2012). Alginate is a naturally occurring biopolymer that is sourced from brown algae (Phaeophyceae), including Ascophyllum nodosum, Laminaria hyperborea, Laminaria japonica, Macrocystis pyrifera, and Laminaria digitate (Aderibigbe and Buyana, 2018). Soluble sodium alginate gel forms as a result of an active ion exchange of calcium ions for sodium ions at the wound surface, resulting in absorption of fluid at the wound site (Aderibigbe and Buyana, 2018).…”
Section: General Description and Physical Propertiesmentioning
confidence: 99%
“…Alginates are processed to form a number of dressing types that vary in their shape and size. They can be adapted to form wafers, nanofibers and topical formulations (Aderibigbe and Buyana, 2018). Alginate dressings are available as freeze-dried porous sheets or flexible fiber dressings.…”
Section: Forms and Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…This polysaccharide is biocompatible, relatively inexpensive, and its formulations have high absorption capacities [39]. These characteristics, associated with the fact that alginate forms gels with structural similarity to the extracellular tissue matrices, make alginate an interesting material for wound dressings [75]. Following, examples of healing action of alginate-based formulations in skin wound infection are provided.…”
Section: Alginate-based Formulationsmentioning
confidence: 99%
“…Furthermore, was well demonstrated that alginate is biocompatible, not toxic and able to reduce bacterial infections [18]. For all these reasons, alginate-based dressings and auto-gelling devices [19] were studied and, in some cases, commercialized [20].…”
Section: Introductionmentioning
confidence: 99%